Assessment of the Impact of Paraquat-Induced Genotoxicity in Sorghum bicolor (Guinea Corn) - Andrew , Oche; Andrew , Mercy; Edache , Samuel (International Journal of Scientific Research in Biological Sciences, 2024)
This study investigated the genotoxicity effects of Paraquat herbicide, a non-selective paraquat-based herbicide, on Deoxyribonucleic acid (DNA) integrity in germinated guinea seeds. The guinea corn seeds were germinated in distilled water medium and then treated with varying concentrations of Paraquat herbicide (0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 and 1.0ml, diluted in 20 ml of water), with three samples per concentration. By day 7, no root emergence was observed, and by day 10, all seedlings showed signs of decay. DNA damage was analyzed using Random Amplified Polymorphic DNA (RAPD) and polymerase chain reaction (PCR) techniques, along with chromosomal analysis for aberrations. Results indicated a dose-dependent genotoxic effect, evidenced by chromosomal fragmentation, micronuclei formation, and DNA strand breaks in treated samples. The findings reveal that high concentrations of Paraquat herbicide significantly compromise Deoxyribonucleic acid (DNA) integrity in guinea corn, raising concerns on the damages and impacts this herbicides can cause on a broader term involving other crop genetics